Monetary policy effects on equity returns: Application of SVAR identified with high-frequency external instrument - Woon Wook Jang (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2021)
The purpose of this study is to examine the effects of monetary policy on equity returns by applying an alternative econometric approach. Campbell and Ammer (1993) decomposed unexpected equity excess returns into three news components: risk premium news, real interest rate news and cash-flow news. The literature has determined the monetary policy (MP) effects on these news components. The authors propose an alternative MP shock identification approach to analyze the MP effects on the above-mentioned news components under a structural vector autoregression (SVAR) setup. Under this approach, one can apply an MP indicator in the SVAR, which helps forecast equity excess returns along with its external instruments for identification. Further, this study uses the various recently proposed measures of exogenous MP shocks and Fed information shocks as external instruments, and shows the different patterns of the news components' responses depending on the information in the applied instruments.
Keywords: E44; E52; E58; G12; 330; Equity return decomposition; Monetary policy effects; Structural vector autoregression; External instruments